The Reliability of Lower Extremity and Thoracic Kinematics at Various Running Speeds - Doma, K.; Deakin, G. B.; Sealey, R. M. (International Journal of Sports Medicine, 2012)
Whilst various studies have examined lower extremity joint kinematics during running, there is limited investigation on joint kinematics at steady-state running and at intensities close to exhaustion. Subsequently, the purpose of this study was to determine whether the reliability of kinematics in the lower extremity and thorax is affected by varying the running speeds during a running economy test. 14 trained and moderately trained runners undertook 2 running economy tests with each test incorporating 3 intensity stages: 70-, 90- and 110% of the second ventilatory threshold, respectively. The participants ran for 10 min during each of the first 2 stages and to exhaustion during the last stage. Kinematics of the ankle, knee, hip, pelvis and thorax were recorded using a 3-dimensional motion analysis system. Intra-class correlation coefficient (ICC), limits of agreement (LOA) and coefficient of variation (CV) were used to calculate reliability. The ICC, LOA and CV of the lower extremity and thoracic kinematic variables ranged from 0.33–0.97, 1.03–1.39 and 2.0–18.6, respectively. Whilst the reliability did vary between the kinematic variables, the majority of results showed minimal within-subject variation and moderate to high reliability. In conclusion, examining thoracic and lower extremity kinematics is useful in determining whether running kinematics is altered with varying running intensities.
Keywords: biomechanics; running; discontinuous; incremental; gait analyses